UCE phylogenomics, biogeography, and classification of long-horned bees (Hymenoptera: Apidae: Eucerini), with insights on using specimens with extremely degraded DNA - Freitas, Felipe V [UNESP]; Branstetter, Michael G; Franceschini-Santos, Vinícius H; Dorchin, Achik; Wright, Karen W; López-Uribe, Margarita M; Griswold, Terry; Silveira, Fernando A; Almeida, Eduardo A. B (Oxford University Press (OUP), 2023)
Long-horned bees (Apidae, Eucerini) are found in different biomes worldwide and include some important crop pollinators. In the Western Hemisphere, Eucerini received extensive taxonomic study during the twentieth century, resulting in several revisions of its genera. In contrast, progress on eucerine phylogenetic research and the genus-level classification has been slow, primarily due to the relatively homogeneous external morphology within the tribe and the rarity of many of its species in collections. Here, we present a comprehensive phylogenetic study of Eucerini based on ultraconserved elements, including 153 species from nearly all genera and subgenera and from all biogeographic regions where they occur. Many of these specimens are from museums and were collected as far back as 1909. We discuss the challenges of working with specimens with highly degraded DNA, present insights into improving phylogenetic results for both species-tree and concatenation approaches, and present a new pipeline for UCE curation (Curation of UltraconseRved Elements - CURE). Our results show the existence of seven main lineages in Eucerini and most of the genera and subgenera to be reciprocally monophyletic. Using a comprehensive and up-to-date phylogenetic framework, we: (1) propose taxonomic changes, including a new subtribal classification and reorganized generic and subgeneric limits; (2) estimate divergence times; and (3) conduct a detailed exploration of historical biogeography of long-horned bees. We find that eucerine lineages expanded their range onto most continents only after their initial diversification in southern South America during the Eocene.
Keywords: CURE; ddBD; MCMCtree; museomics; UCE curation